Economic Policies of Pakistan during Democratic Governments (1947-2012): An Analytical Study in Islamic Perspective - Sadia Gulzar; Mumtaz Ahmed Salik (jihat-ul-islam, 2019)
In the history of Pakistan, democratic governments ruled for a long period of time but they did not make stable policies for its economic development. A certain class got economic benefits whereas masses remained deprived of basic necessities of life. Public welfare got secondary importance which resulted in economic disparity. In Islamic state, it is the responsibility of a ruler to provide individuals with basic necessities of life and to circulate wealth. Democratic governments relied on conditional external economic assistance which not only increased the burden of debt but also affected our social values. Economy of Pakistan challenged the problems such as foreign trade imbalance, external debt and its liabilities, high aggregate demand, slow GDP growth, poverty, poor rate of literacy, high unemployment rate and poor health care facilities etcetera. Pakistan could develop, if any of the governments might have followed Islamic economic principles. This research paper followed descriptive and analytical methods.